Drug reaction with eosinophilia and systemic symptoms (DRESS) with acute kidney injury and transaminitis: A rare case - Luziani, Stefani; Roslina, Nina; Zakaria, Rio; Sumarmi (Bali Dermatology Venereology and Aesthetic Journal, 2025)
Background: Drug reaction with eosinophilia and systemic symptoms (DRESS) is a rare, serious, and potentially life-threatening drug hypersensitivity reaction. The diagnosis of DRESS can be challenging to make because of the highly variable clinical presentation, progressive onset of manifestations, and the extended period from drug exposure to onset. Many DRESS cases remain undiagnosed or misdiagnosed. This study aims to report a rare case of an adult patient with DRESS to expand our knowledge and avoid delayed identification and treatment. Case: A 31-year-old male presented to the emergency department with a chief complaint of itchy, red desquamation rashes all over his body, with fever and swelling on his face. The dermatological status obtained was a generalized distribution; on nearly the entire body surface area, there were multiple lesions, confluent, with unclear boundaries, irregular in shape, plaque-sized, not raised, dry, in the form of erythematous macules with scales and light yellow crusts. Hematological laboratory analysis revealed hypereosinophilia. The renal function indicated a decreased eGFR of over 75%, and the hepatic function test revealed an elevated in liver function. The patient was diagnosed with DRESS, acute kidney injury, and transaminitis. There was an improvement in the patient's condition following the withdrawal of the previous medications and the administration of intravenous dexamethasone, oral antihistamine, and symptomatic treatment. Conclusion: Early identification and withdrawal of all suspected medications are essential for the management of DRESS, as a delayed diagnosis can be life-threatening. The administration of systemic steroids is efficacious for the treatment of DRESS.